Penerapan Diversifikasi Produk Perikanan di Desa Darunu, Kabupaten Minahasa Utara - Damongilala, Lena Jeane; Salindeho, Netty (Sam Ratulangi University, 2020)
Community Partnership Program (PKM) is an activity to empower community members as a form of partnership among academia, the community and the government. The program aims to improve the skills, production and welfare of the community. The program's target partners are located in the village of Darunu, Wori District, North Minahasa Regency. Geographically located on the coast with potential for marine fisheries that have the potential to be developed. The village is categorized as a fishing community, where around 30% are classified as poor families and have a small business as fish sellers of fish processors. The specific target of activities is to produce superior diversified products in terms of taste, sanitation and hygiene, as well as to provide business continuity for diversification of fish meatball products, dragon legs, and fish nuggets. The issue that has to be solved is that how to utilize Â fishery products Â during abundant harvests. The methods applied in this program are 1) Training of how to produce fish products using good manufacturing practices; Â 2) Mentoring and evaluation on the way the partners handling fish product.